Crystal boundary engineering‐dominated high‐performance chitosan‐based triboelectric nanogenerator for self‐powered breath‐activated ammonia sensors - Fayang Wang; Pengfan Wu; Xin Chen; Endian Cui; Tao Liu; Xiaojing Mu; Ya Yang (InfoMat, 2025)
Abstract Triboelectric nanogenerators (TENGs) as a clean energy‐harvesting technology are experiencing significant growth in the pursuit of carbon neutrality, accompanied by the increasing use of environmentally friendly biomaterials. However, biomaterials exhibit inferior triboelectric properties compared with petro‐materials, hindering the development of bio‐based TENGs. Here, leveraging the crystal boundary‐tuning strategy, we develop a chitosan aerogel‐based TENG (CS‐TENG) that is capable of delivering power density over 116 W m–2, beyond that of the previous reports for CS‐TENG by an order of magnitude. With a high output voltage of 3200 V, the CS‐TENG directly illuminated 1000 LEDs in series. Notably, the CS aerogel exhibits self‐healing, waste recycling and gas‐sensitive properties, ensuring the long‐term durability, environmental benignity and sensing characteristics of the CS‐TENG. Furthermore, a breath‐activated mask‐integrated CS‐TENG ammonia monitoring system is engineered, which accurately detects changes in ammonia concentration within the range of 10–160 ppm, enabling real‐time monitoring of ammonia in the environment. Our results set a record for the ultrahigh power density of CS‐TENG, representing a significant advancement in the practical application of TENGs.